Horn growth appears to decline under intense trophy hunting, but biases in hunt data challenge the interpretation of the evolutionary basis of trends. (5th May 2021) - Morrissey, Michael B.; Hubbs, Anne; Festa‐Bianchet, Marco
Abstract: A recent article in Evolutionary Applications by LaSharr et al. reports on trends in the size of horns of bighorn sheep ( Ovis canadensis ) throughout much of the species' range. The article concludes that there are "... stable or increasing trends in horn growth over nearly 3 decades in the majority of hunt areas throughout the western U.S. and Canada." However, the article equates nonsignificance of predominantly negative trends in the areas with the most selective harvest as evidence for the null hypothesis of no trends and also fails to consider well‐known and serious biases in the use of data collected in size‐regulated hunts. By applying meta‐analysis to the estimates reported by LaSharr et al., we show that there has been a pervasive overall trend of declining horn sizes in Alberta, where the combination of horn size‐based legality, combined with unrestricted hunter numbers are understood to generate the greatest selective pressures. Given the nature of the biases in the underlying data, the magnitudes of the trends resulting from our re‐analysis of LaSharr et al.'s ( Evolutionary Applications, 2019, 12, 1823 ) trend estimates are probably underestimated.